2008
DOI: 10.1080/14786430701846214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new quaternary chalcogenide As–Ge–Se–Sb thin films

Abstract: This paper reports the effect of replacement of selenium by antimony on the optical gap and some other physical parameters of new quaternary chalcogenide As 14 Ge 14 Se 72Àx Sb x (where x ¼ 3, 6, 9, 12 and 15 at%) thin films. Thin films with thickness 200-220 nm of As 14 Ge 14 Se 72Àx Sb x were prepared by thermal evaporation of the bulk samples. Increasing antimony content was found to affect the average heat of atomization, the average coordination number, number of constraints and cohesive energy of the As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 30 publications
3
39
1
Order By: Relevance
“…It was found that the variation in the theoretical values of the energy gap (E th g ) with composition for ternary alloys can be described by the following relation [20]:…”
Section: Cohesive Energy Of the Systemmentioning
confidence: 99%
“…It was found that the variation in the theoretical values of the energy gap (E th g ) with composition for ternary alloys can be described by the following relation [20]:…”
Section: Cohesive Energy Of the Systemmentioning
confidence: 99%
“…The decreasing in average bond energy: according to the chemical bond approach proposed by Bicerano and Ovshinsky [19], the interatomic bonds are formed in the sequence of decreasing in total bond energy until the available valence of atoms is satisfied. Thus, by increasing the arsenic content, some of the stronger Ge-Se (49.44 kcal/mol) and Sb-Se (43.97 kcal/mol) bonds have been replaced with weaker As-Se (41.69 kcal/mol) bond [5]. By this replacement, the average bond energy of glassy network has been decreased and the formed glasses show lower thermal stability.…”
Section: Resultsmentioning
confidence: 94%
“…In the second region, the absorptions is related to transitions from the localized tail states above the valence band edge to extended states in the conduction band and/or from extended states in the valence band to localized tail states below the conduction band. The spectral dependence of absorption coefficient usually follows the so-called Urbach rule: U h exp( ) E u a=b (5) By attention to these equation, and least square fitting of Ln α against hν curves in the tailing part of localized states [24], the Urbach energy (E U ) can be calculated as shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
“…The compositional dependence of the average coordination number and the overall mean bond energy in the covalent network of Ge 20 Se 60 Sb 20 − x Ag x glasses has been obtained. The coordination number (the number of the nearest-neighbor atoms) for Ge, Se, Sb and Ag is given in Table 1 [1,15]. Values of the average coordination number in the system Ge 20 Se 60 Sb 20 − x Ag x (where x = 0, 5, 10, 15 and 20 at.%) are calculated from the eq.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, chalcogenide glasses exhibit a continuous change of their properties by changing their chemical structure. Such studies on characterization [1], crystallization kinetics [2,3] and optical constants [4,5] have recently been reported.…”
Section: Introductionmentioning
confidence: 99%